Evaluation of Pharmacovigilance Awareness Among Healthcare Providers and Patients: A Field Study - Wadiaa Benamer; Mustafa Targhi; Marwa Farhat; Safa Mosa (Khalij-Libya Journal of Dental and Medical Research, 2025)
People use medicines at some point in their lives, so they need to understand what they are taking and the risks involved. With about over half a million medicinal product groups on the worldwide market, there’s an almost infinite number of ways in which harm can arise from treatments themselves or from interactions between them, as well as, from dietary, environmental and gastric factors in addition, poor quality and fake medicines are also constant treats in many parts of the world, however, using of medicinal products have benefit and risk effects and, due to the many repeated mistakes and disasters that are associated with drugs’ use and related products led the need of pharmacovigilance follow up. Pharmacovigilance (PV) supports safe and appropriate uses of drugs after marketing and use by a population. The spontaneous reporting system of Adverse Drug Reaction (ADR) is an essential component of pharmacovigilance; however, significant underreporting of ADR remains a major problem in developing countries. Knowledge of PV could form the basis for interventions aimed at improving reporting rates and consequently decreasing ADRs. This cross-sectional descriptive study was carried out to gain knowledge on how familiar health care providers and the relevant administration of the Ministry of Health are with the concept of pharmacovigilance. The study involved distributing a questionnaire form and interviews of 205 randomly selected persons (60 physicians, 75 pharmacists, 30 nurses, and 40 patients). The study showed significant number of health care providers have incomplete information on the concept of PV and how it is integrated into health care system, much less its purposes and the necessity to report ADRs during professional practice, in contrast, the pharmacists in general have much more information and awareness on PV, particularly those working with Ministry of Health in the Pharmacy and Medical Equipment Administration. Concerning the patients, unfortunately, neither the physicians nor the pharmacists were keen enough to advise their patients on how to differentiate between the expected side effects and the unexpected ADRs.